EFEKTIVITAS BERBAGAI KONSENTRASI NEMATODA ENTOMOPATOGEN (Steinernema sp) TERHADAP MORTALITAS LARVA Spodoptera exiqua Hubner - Ria, Kamariah; Natsir, Burhanuddin; Panggeso, Johanis (AGROTEKBIS, 2013)
Spodoptera exiqua is known as onion caterpillar, it attacks often reduces onion production. This insect could even cause harvest failure, and chemicals in high doses and spraying is often used to control on its spread. This action can negatively impact to environment as well the users. To reduce the negative impact of the use of chemical insecticides is necessary to find an alternative strategy. It is known that several biological agents could serve as biopesticides such as entomopathogenic nematodes Steinernema sp. This study was aimed to determine effective concentration of entomopathogenic nematodes Steinernema sp. to control S. exiqua growth. Nematode used in this study was Infective juvenile (IJ) instar II. There were 6 different nematodes concentrations as treatments and each treatment was repeated 4 times in a Completely Randomized Design (CRD). The treatments were 0 IJ, 200 IJ, 400 IJ, 600 IJ, 800 IJ, and 1000 IJ of nematodes, mixed in 2 ml of distilled water, respectively. The results showed that the concentration of nematodes 600 JI is effective to kill 83.4% larvae of S. exiqua within 6 days. This finding clearly shows that nematode is able to reduce larvae S.exiqu and expecting a positive impact to onion production.